Efficacy and safety of denosumab and teriparatide versus oral bisphosphonates to treat postmenopausal osteoporosis: a systematic review and meta-analysis - Yang, Jia; Guo, Xiaobo; Cui, Zhongning; Guo, Huikang; Dong, Jia-Nan (Frontiers in Endocrinology, 2024)
Study Design: A systematic review and Meta-analysis Objective: To compare the efficacy and safety of denosumab and teriparatide versus oral bisphosphonates to treat postmenopausal osteoporosis. Summary of Background Data: While bisphosphonates have historically been the cornerstone of pharmacological management for bone protection in patients, emerging evidence suggests that teriparatide and denosumab warrant further investigation as potential first-line treatments. The optimal choice among denosumab, teriparatide, and oral bisphosphonates for the treatment of postmenopausal osteoporosis remains a subject of ongoing debate and controversy within the scientific community. Methods: This systematic review adhered meticulously to the rigorous standards outlined by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines as well as the Cochrane Collaboration recommendations. Additionally, it employed the AMSTAR (Assessing the methodological quality of systematic reviews) criteria to ensure methodological robustness and enhance the credibility of the findings. A systematic electronic search was conducted across Web of Science, PubMed, and the Cochrane Library databases from their inception dates up to February 2024. Results: In this meta-analysis of studies, our findings suggest that compared to bisphosphonates, both teriparatide and denosumab demonstrated notable increases in percentage changes in lumbar spine bone mineral density (BMD) among postmenopausal osteoporosis patients. Furthermore, denosumab exhibited superiority over teriparatide and oral bisphosphonates in enhancing percentage changes in both femoral neck and total hip BMD, indicating its potential as a more efficacious option. Regarding safety outcomes, no significant differences were observed in the incidence of serious adverse events among patients treated with teriparatide, denosumab, and bisphosphonates. However, teriparatide showed superiority over oral bisphosphonates in terms of a lower risk of general adverse events, suggesting a favorable safety profile.In conclusion, our study suggests that teriparatide and denosumab demonstrate comparable or potentially superior efficacy and safety profiles compared to oral bisphosphonates for the treatment of postmenopausal osteoporosis.